Pelatihan Metode Pengukuran Capaian Pembelajaran Kurikulum Prodi Teknik Sipil Berbasis Outcome Based Education (OBE) pada Anggota BMPTTSSI - Muhammad Isran Rarmli; M A Thaha .; M W Tjaronge . (Faculty of Engineering UNHAS, 2022)
Technology and communication growing rapidly, without being supported by human resources it becomes a challenge in education especially in higher education. One of the issues facing today is the education process, the world of work, and the need for innovation. New design in curriculum is using the Outcome Based Education (OBE) system approach. This system is one of education system that focuses on learning outcomes with measurable final results or outcomes. Introducing OBE system and assessment method in training workshops is one of the methods to make people knowing briefly. The main output of this activity is the increased level of understanding of BMPTTSSI members regarding OBE system and understanding of program educational objectives of study program performance. Participants who participated in the training enthusiastically and realized that the methods that had been used so far could be modified in such a way that the output targets given to the related courses could be assessed. This training provides benefits for the Department of Civil Engineering Faculty of Engineering Universitas Hasanuddin, especially the measurement of Course Learning Outcomes (CLO) and how it is implemented. All participants have been more discussion and sharing about how to collaborate in achieving the CLO assessment according to OBE system.